2018
DOI: 10.1021/acs.molpharmaceut.8b00126
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Canine Oral Melanoma with Nanotechnology-Based Immunotherapy and Radiation

Abstract: The presence and benefit of a radiation therapy-associated immune reaction is of great interest as the overall interest in cancer immunotherapy expands. The pathological assessment of irradiated tumors rarely demonstrates consistent immune or inflammatory response. More recent information, primarily associated with the "abscopal effect", suggests a subtle radiation-based systemic immune response may be more common and have more therapeutic potential than previously believed. However, to be of consistent value,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 34 publications
3
95
0
Order By: Relevance
“…We further verified the immunotherapeutic efficacy of CPMV in separate studies in the treatment of murine dermal melanoma [110], intracranial glioma [111] and ovarian cancer [109]. In addition to the mouse studies, we have begun testing the immunotherapy in canine patients, and our data indicate similar efficacy in these patients [112]. In the aforementioned CPMV studies, the immunotherapeutic vaccines are administered multiple times; however, multiple dosing regimens can lead to low patient compliance and increased hospital burden.…”
Section: Vlps As Monotherapymentioning
confidence: 72%
See 1 more Smart Citation
“…We further verified the immunotherapeutic efficacy of CPMV in separate studies in the treatment of murine dermal melanoma [110], intracranial glioma [111] and ovarian cancer [109]. In addition to the mouse studies, we have begun testing the immunotherapy in canine patients, and our data indicate similar efficacy in these patients [112]. In the aforementioned CPMV studies, the immunotherapeutic vaccines are administered multiple times; however, multiple dosing regimens can lead to low patient compliance and increased hospital burden.…”
Section: Vlps As Monotherapymentioning
confidence: 72%
“…Indeed, combining radiation therapy with CPMV in situ vaccination significantly improved tumor growth delay in ID8-Def29/Vegf-A-Luc tumors compared to either therapy alone [121]. The potent efficacy of CPMV + radiation therapy has also been translated to canine patients with melanoma [112]; therefore, this approach demonstrates high translational potential.…”
Section: Vlps In Combination Therapymentioning
confidence: 99%
“…In all cases, the combination led to enhanced survival and prolonged tumor suppression compared to either treatment alone. VLP administration combined with radiation therapy has been validated in a canine preclinical trial with impressive results . All canine patients treated with this combination became tumor‐free, firmly supporting the clinical potential of VLPs as a therapeutic modality against cancer.…”
Section: Biomimetic Anticancer Nanovaccinesmentioning
confidence: 77%
“…More recently we demonstrated that the immunostimulatory properties of VNPs can be harnessed also in the context of tumors: when applied as in situ vaccine, the VNPs formed by the cowpea mosaic virus (CPMV) reverse the immunosuppressive tumor microenvironment and promote the antigen‐presenting ability of innate immune cells, therefore restarting the cancer immunity cycle . Preclinical data in several mouse models indicate potent efficacy; we also demonstrated the translational potential by successfully treating canine patients with spontaneous melanoma using a combination of CPMV in situ vaccination and radiation therapy …”
mentioning
confidence: 87%